Nanomaterial‐Modified Conducting Paper: Fabrication, Properties, and Emerging Biomedical Applications. Issue 12 (9th September 2019) - Kumar, Saurabh; Pandey, Chandra Mouli; Hatamie, Amir; Simchi, Abdolreza; Willander, Magnus; Malhotra, Bansi D.
Abstract: The emerging demand for wearable, lightweight portable devices has led to the development of new materials for flexible electronics using non‐rigid substrates. In this context, nanomaterial‐modified conducting paper (CP) represents a new concept that utilizes paper as a functional part in various devices. Paper has drawn significant interest among the research community because it is ubiquitous, cheap, and environmentally friendly. This review provides information on the basic characteristics of paper and its functionalization with nanomaterials, methodology for device fabrication, and their various applications. It also highlights some of the exciting applications of CP in point‐of‐care diagnostics for biomedical applications. Furthermore, recent challenges and opportunities in paper‐based devices are summarized. Abstract : The basic characteristics of paper and its functionalization with nanomaterials, as well as methodology for device fabrication and their various applications are presented. It also highlights some of the exciting applications of conducting paper in point‐of‐care diagnostics for biomedical applications. Furthermore, recent challenges and opportunities in the development of paper‐based devices are summarized.